Antioxidant of Effervescent Tablet Formulated from Combination of Secang Wood and Red Ginger Extracts - Sofyah, Titik Mardiyanti; Tukiran, Tukiran; Sutoyo, Suyatno (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Secang wood has strong antioxidant properties because it contains phenolic compounds such as flavonoids and brazilin. Also, red ginger has antioxidant derived from nonvolatile phenolic compounds. Until now, there has been no use of a combination of secang wood extract and red ginger specifically for the manufacture of effervescent tablets. The purpose of this study was to formulate an effervescent tablet by doing combination of secang wood and red ginger extracts with using various concentrations of citric and tartaric acids. The formulations conducted were three acid sources of 20%, 25%, 30%, using wet granulation. The evaluation subjected to the formulas included the physical properties of the granules, such as the water content and flow properties of the granules. Meanwhile, the evaluation performed to the tablet included the hardness test, tablet friability, weight uniformity, dissolution time, and acidity (pH). The analysis was carried out in accordance with the requirements of the Indonesian Pharmacopoeia Edition III and BPOM. The results obtained are effervescent tablet with an acid variation of 20% with physical quality values of water content of 2.91% and granule flow properties of 6.03 s. Meanwhile, the physical quality requirements of effervescent tablets were tablet hardness of 4.02 kp; tablet friability 0.46%; weight uniformity 0.132%; 71 s dissolution time; and 6.4 degrees of acidity.